Metaverso y Propiedad Intelectual - León y León, Gustavo (2023)
The idea of the article is to analyze the problems that Intellectual Property must face in the areas of Trademark Law, Inventions and Copyright in the metaverse, that is, in the virtual universe where human beings interact socially and economically as avatars through software in cyberspace. Glimpsing a strong and accelerated raise of the so-called Web3, important companies such as Facebook, Inc., have opted to change their name and direct all their future developments towards the growth of the metaverse that they consider to be the next step in the social connections. However, this virtual universe entails several challenges to Intellectual Property since the legal systems conceived for the physical world cannot always be faithfully adapted to the virtual environment.